A. \(6x + 3y + 2z - 24 = 0\)
B. \(6x + 3y + 2z - 12 = 0\)
C. \(6x + 3y + 2z = 0\)
D. \(6x + 3y + 2z - 36 = 0\)
A
Phương trình mặt phẳng \(\left( {ABC} \right)\) là: \(\dfrac{x}{2} + \dfrac{y}{4} + \dfrac{z}{6} = 1 \Leftrightarrow 6x + 3y + 2z - 12 = 0\)
\(//\left( {ABC} \right) \Rightarrow \left( P \right):\) \(6x + 3y + 2z + m = 0,\,\left( {m \ne - 12} \right)\)
\(d\left( {D;\left( P \right)} \right) = \dfrac{{\left| {6.2 + 3.4 + 2.6 + m} \right|}}{{\sqrt {{6^2} + {3^2} + {2^2}} }} = \dfrac{{\left| {36 + m} \right|}}{7}\)
\(d\left( {\left( {ABC} \right);\left( P \right)} \right) = d\left( {A;\left( P \right)} \right) = \dfrac{{\left| {6.2 + 3.0 + 2.0 + m} \right|}}{{\sqrt {{6^2} + {3^2} + {2^2}} }} = \dfrac{{\left| {12 + m} \right|}}{7}\) (do \(\left( P \right)//\left( {ABC} \right)\))
Theo đề bài, ta có:
\(\dfrac{{\left| {36 + m} \right|}}{7} = \dfrac{{\left| {12 + m} \right|}}{7} \Leftrightarrow \left| {36 + m} \right| = \left| {12 + m} \right| \Leftrightarrow \left[ \begin{array}{l}36 + m = 12 + m\,\,\left( {vo\,\,nghiem} \right)\\36 + m = - 12 - m\end{array} \right. \Leftrightarrow m = - 24\,\,\left( {tm} \right)\)
Vậy, \(\left( P \right):6x + 3y + 2z - 24 = 0\).
Chọn: A
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247